2013
DOI: 10.1371/journal.pone.0064188
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Prorocentrum donghaiense Blooms and the Taiwan Warm Current in the East China Sea - Evidence for the “Pelagic Seed Bank” Hypothesis

Abstract: During the last two decades, large-scale high biomass algal blooms of the dinoflagellate Prorocentrum donghaiense Lu have occurred frequently in the East China Sea (ECS). The role of increasing nutrient concentrations in driving those blooms is well-established, but the source population that initiates them is poorly understood. We hypothesized that the front of Taiwan Warm Current (TWC) may serve as a ‘seed bank’ that initiates P. donghaiense blooms in the ECS, as the physiochemical conditions in the TWC are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 18 publications
(30 reference statements)
1
23
0
Order By: Relevance
“…However, the abundance‐based approach has its limitations that it might not work well in distinguishing algal blooms of different PSCs with the same chlorophyll concentration, since it assumes that larger cells dominate in higher concentrations and smaller cells in low concentrations. Many studies found that microplankton such as dinoflagellates were the most common dominances along coastal waters in the study area (e.g., Dai et al, ; Lou & Hu, ; Xia et al, ; Zhou et al, ) which confirmed the assumptions of the abundance‐based model. Although there are few reports, there is the possibility that small size or mixed sizes phytoplankton blooms could exist.…”
Section: Discussionsupporting
confidence: 76%
“…However, the abundance‐based approach has its limitations that it might not work well in distinguishing algal blooms of different PSCs with the same chlorophyll concentration, since it assumes that larger cells dominate in higher concentrations and smaller cells in low concentrations. Many studies found that microplankton such as dinoflagellates were the most common dominances along coastal waters in the study area (e.g., Dai et al, ; Lou & Hu, ; Xia et al, ; Zhou et al, ) which confirmed the assumptions of the abundance‐based model. Although there are few reports, there is the possibility that small size or mixed sizes phytoplankton blooms could exist.…”
Section: Discussionsupporting
confidence: 76%
“…Microorganisms can travel long distances by hitchhiking on ocean currents, influencing microbial community assemblies (Brum et al., ; Doblin & van Sebille, ) from prokaryotes (Hamdan et al., ; Zhao et al., ) to microeukaryotes (Pernice et al., ). Previous studies have reported algae and plankton as intruders in the ECS through the KSWM (Dai et al., ; Hsieh et al., ). Here, the KSWM also appears responsible for fungal dispersal, as highlighted by the high occurrence of OTU_26404 (close affiliation with Aspergillus nidulans ) in the KSWM and TWM and the low occurrence in the CWM.…”
Section: Discussionmentioning
confidence: 97%
“…The huge nutrient input (organic and inorganic compounds) by coastal rivers and Kuroshio water greatly influences the diversity and distribution patterns of many microorganisms in the ECS including planktonic bacteria, microalgae and zooplankton (e.g., Dai et al., ; Hsieh et al., ; Zhao et al., ). For example, Synechococcus and picoeukaryotes abundance was found to covary with nutritional conditions such as the NO 3 − , NO 2 − , PO 4 3− and SiO 3 2− concentrations (Zhao et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, compared to the southward flowing ZMCC, the direction and velocity of the TWC are relatively stable, flowing northeastward with annual mean speed about 14 cm s 21 , and seasonal mean speed about 13 and 17 cm s 21 in winter and summer, respectively [Guan and Fang, 2006]. As one of major currents in the ECS, the TWC has an overwhelming influence on the heat, salt, and nutrients balance on the ECS shelf [Fang et al, 1991;Guan and Fang, 2006;Chen, 2009], and to some extent results in upwelling, hypoxia, and algal bloom in the Changjiang Estuary and adjacent shelf areas [Qiao et al, 2006;Wei et al, 2007;Wang, 2009;Dai et al, 2013]. Despite the significant influence of the TWC on the shelf environment and ecosystem, its origin and flow pathway have been intensely debated over the last several decades.Early hydrographic surveys suggest that the TWC originates from the branching of Kuroshio Current northeast of Taiwan [Uda, 1934;Mao et al, 1964], while Guan [1984 pointed out that in summer it should stem in the Taiwan Strait and flows northeastward based on the historical current data from 1932 to 1977 (Figure 1a).…”
mentioning
confidence: 99%